Lattice Boltzmann modeling of bubble formation and dendritic growth in solidification of binary alloys. (March 2016) - Sun, Dongke; Zhu, Mingfang; Wang, Jun; Sun, Baode
Highlights: A model coupling the multi-relaxation-time (MRT)-lattice Boltzmann (LB) and the cellular automaton (CA) methods has been developed to study dendritic growth and bubble formation. The present model using the MRT based single-component multiphase (SCMP) scheme is obviously of better performance than the previously developed CA-multicomponent multiphase model. This work reveals the cooperative–competitive relationship between the dendritic growth and the bubble formation during the solidification of alloys. It would like to provide a reliable numerical approach to study the interacting mechanism between dendrites and bubbles. Abstract: The cellular automaton (CA)–lattice Boltzmann (LB) coupled model is extended to three dimensions to study bubble formation and dendritic growth of binary alloys. The coupled model, with implicitly embedding the dendrite–bubble interaction, accounts for the gas precipitation and liquid–gas transition by the LB Shen–Chen scheme. Model validation is performed by simulating the Laplace law and the contact angle, and agreements are well-shown between simulation data and analytical expressions. Simulations of directional solidification is then carried out, reproducing several essential physical phenomena, including the nucleation of bubbles at the liquid/solid interface and the precipitation of small bubbles in the inter-dendritic region, which coincide qualitatively with the in situ experimental observation. There exist cooperative and competitive relationships between the dendritic growth and the bubble formation during solidification. The dendritic growth promotes the bubble nucleation at the initial stage, while a competition rises up at the latter stage. Altering the initial liquid density can obviously change the final microstructure, but hardly significantly influence the macroscopic statistical trends of solidification.